Optimal integration of kinematic and ball-flight information when perceiving the speed of a moving ball - Nakamoto, Hiroki; Fukuhara, Kazunobu; Torii, Taiga; Takamido, Ryota; Mann, David L. (Frontiers in Sports and Active Living, 2022)
In order to intercept a moving target such as a baseball with high spatio-temporal accuracy, the perception of the target's movement speed is important for estimating when and where the target will arrive. However, it is unclear what sources of information are used by a batter to estimate ball speed and how those sources of information are integrated to facilitate successful interception. In this study, we examined the degree to which kinematic and ball-flight information are integrated when estimating ball speed in baseball batting. Thirteen university level baseball batters performed a ball-speed evaluation task in a virtual environment where they were required to determine which of two comparison baseball pitches (i.e., a reference and comparison stimuli) they perceived to be faster. The reference and comparison stimuli had the same physical ball speed, but with different pitching movement speeds in the comparison stimuli. The task was performed under slow (125 km/h) and fast (145 km/h) ball-speed conditions. Results revealed that the perceived ball-speed was influenced by the movement speed of the pitcher's motion, with the influence of the pitcher's motion more pronounced in the fast ball-speed condition when ball-flight information was presumably less reliable. Moreover, exploratory analyses suggested that the more skilled batters were increasingly likely to integrate the two sources of information according to their relative reliability when making judgements of ball speed. The results provide important insights into how skilled performers may make judgements of speed and time to contact, and further enhance our understanding of how the ability to make those judgements might improve when developing expertise in hitting.